Mindful Transportation: A Conceptual Framework for Enhancing Accessibility for People with Disabilities in Malaysia - Juhari, Joeaiza; Yahya, Wan Kalthom; Rahim, Najihah Abdul; Husin, Norhusniyati; Daud, Siti Rohana (Information Management and Business Review, 2024)
This conceptual paper explores the integration of mindfulness principles into the development of transportation services for people with disabilities (PWDs) in Malaysia. Transportation plays a critical role in promoting inclusivity and enhancing the quality of life for PWDs, yet accessibility remains a significant challenge due to infrastructural barriers, lack of awareness, and limited empathy from service providers. Drawing on the concepts of mindfulness, which are rooted in awareness, empathy, and responsiveness, this paper proposes a framework that emphasizes inclusivity, respect, and collaboration among key stakeholders. The proposed framework emphasizes the need for a holistic approach that incorporates physical accessibility, staff training, and policy reforms. Inclusivity involves modifying infrastructure to meet universal design standards, while empathy requires transport providers to understand the unique challenges faced by PWDs and offer compassionate, tailored services. Responsiveness, a key element of mindfulness, calls for flexible and adaptive transport services that cater to the real-time needs of PWDs, ensuring that they can access public transportation with ease and dignity. By applying this mindful approach, the transportation system can become more accommodating and respectful toward PWDs, thereby reducing social exclusion and improving their mobility. This paper contributes to the growing body of literature on disability inclusion and provides actionable strategies for policymakers, transport providers, and disability organizations to work together in creating a more accessible public transportation system. Future research should investigate the practical application of this framework and its potential to drive policy changes that benefit PWDs across Malaysia.